Improved Method for Ex Ovo-Cultivation of Developing Chicken Embryos for Human Stem Cell Xenografts. (11th March 2013) - Schomann, Timo; Qunneis, Firas; Widera, Darius; Kaltschmidt, Christian; Kaltschmidt, Barbara
Abstract : The characterization of human stem cells for the usability in regenerative medicine is particularly based on investigations regarding their differentiation potential in vivo . In this regard, the chicken embryo model represents an ideal model organism. However, the access to the chicken embryo is only achievable by windowing the eggshell resulting in limited visibility and accessibility in subsequent experiments. On the contrary, ex ovo -culture systems avoid such negative side effects. Here, we present an improved ex ovo -cultivation method enabling the embryos to survive 13 days in vitro . Optimized cultivation of chicken embryos resulted in a normal development regarding their size and weight. Our ex ovo -approach closely resembles the development of chicken embryos in ovo, as demonstrated by properly developed nervous system, bones, and cartilage at expected time points. Finally, we investigated the usability of our method for trans-species transplantation of adult stem cells by injecting human neural crest-derived stem cells into late Hamburger and Hamilton stages (HH26–HH28/E5—E6) of ex ovo -incubated embryos. We demonstrated the integration of human cells allowing experimentally easy investigation of the differentiation potential in the proper developmental context. Taken together, this ex ovo -method supports the prolonged cultivation of properly developing chicken embryos enabling integration studies of xenografted mammalian stem cells at late developmental stages.